LITERATURE REVIEW PENGARUH PROFITABILITAS, SOLVABILITAS, DAN KEPEMILIKAN AUDIT INSTITUSIONAL TERHADAP AUDIT DELAY - Mohammad Ibnu Seina Mulyana; Cris Kuntadi (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The literature review article is the effect of profitability, solvency, and institutional ownership on audit delay. Writing scientific articles that aim to determine the hypothesis of the influence between variables that can be used for further research. In the method of writing scientific articles, namely using qualitative descriptive methods and library research sourced from Google Scholar, E-books and other online media. The results of writing this literature review article are: profitability has a positive effect on audit delay, solvency has a positive effect on audit delay and institutional ownership has a negative effect on audit delay, in a study of audit literature. The results of this literature review article are: 1) Profitability has an effect on audit delay; 2) solvency has an effect on audit delay; and 3) institutional ownership has an effect on audit delay.